2021
DOI: 10.31937/manajemen.v13i1.1929
|View full text |Cite
|
Sign up to set email alerts
|

E-Wallet Service Innovation, Service Delivery, and Customer Satisfaction on Customer Loyalty Within Shopeepay in Indonesia

Abstract: Abstract- Indonesia's fast-growing digital payment industry is encouraging the emergence of new players. In a highly competitive industry and accompanied by COVID-19, e-wallet service providers compete to attract consumers and seller partners to use their services. This study aims to examine the effect of service innovation (SI), service delivery (SD), and customer satisfaction (CS) on customer loyalty (CL) of ShopeePay e-wallet users in Indonesia, especially during the COVID-19 outbreak. This study uses a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
4
0
1
Order By: Relevance
“…First, the perceived risk factor (perceived risk), according to [9] in her research, it is stated that behavioral intention (interest in use) is positively influenced by perceived risk, besides that Fitriani's (2017) in her research states that perceived risk does not significantly affect behavioral intention. Furthermore, the perceived cost factor (perceived cost), [10]in his research states that the perceived cost factor affects behavioral intention significantly, besides that [11] states that perceived cost has no significant effect on behavioral intention. Third, is the factor of perceived trust or perception of trust [12] while stating that perceived trust significantly affects behavioral intention.…”
Section: Introductionmentioning
confidence: 99%
“…First, the perceived risk factor (perceived risk), according to [9] in her research, it is stated that behavioral intention (interest in use) is positively influenced by perceived risk, besides that Fitriani's (2017) in her research states that perceived risk does not significantly affect behavioral intention. Furthermore, the perceived cost factor (perceived cost), [10]in his research states that the perceived cost factor affects behavioral intention significantly, besides that [11] states that perceived cost has no significant effect on behavioral intention. Third, is the factor of perceived trust or perception of trust [12] while stating that perceived trust significantly affects behavioral intention.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have shown that perceived e-service quality is positively related to behavioral and attitudinal loyalty. Furth more, in the finance fields, Valencia and Layman (2021) investigated the relationship between e-wallet service innovation, service delivery, and consumer satisfaction on consumer loyalty. Muharam et al (2021) defined that there is a positive relationship between e-service quality and consumer trust in e-commerce.…”
Section: Trust and Loyaltymentioning
confidence: 99%
“…Measures in this study were supplemented and modified based on previous research. First, the measurement items for characteristics of service quality have been adopted from previous studies (Moon et al, 2021;Esmaeili et al, 2021;Valencia and Layman, 2021;Muharam et al, 2021). Each component has been adapted to prepare the purpose of the study.…”
Section: Research Model and Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Katadata Insight Center telah melakukan riset mengenai jumlah pengguna dari e-wallet (dompet digital) yang menunjukkan angka 9,1% (Amelia and Isbanah 2021). Layanan e-wallet di Indonesia melalui riset yang dilakukan oleh Ipsos mengemukakan bahwa ShopeePay menjadi favorit masyarakat karena pelayanannya di angka 82%, lalu disusul OVO dengan tingkat kepuasan 77%, Gopay 71%, Dana 69%, dan terakhir Link Aja 67% (Valencia and Layman 2021).…”
Section: Pendahuluanunclassified